If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -3 = 0 Reorder the terms: -3 + 3y = 0 Solving -3 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 3y = 0 + 3 3y = 0 + 3 Combine like terms: 0 + 3 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 10y-6+4y=8y-90 | | 2y^2+3=21 | | 4x+9=-47-10 | | (x-8)(5x+6)=(x-10)(4x+3) | | 3y^2-2y-16=0 | | 106-4x=2x+16x | | x^2+2x-6=3x+12 | | 8u=-32 | | 171-3x=24x-24 | | 5u+14=59 | | x^2+2x-6=3x+y+12 | | 262=192-x | | 5(x+2)=-(x+14) | | 5-8x=50-43x | | (3)+(-7)+(11)=x | | 4u+5=-15 | | 0.4x+1.2=4.8 | | 0.3x+1.4(2x-5)=-22.5 | | .5+9x=1 | | 4x+1+5-2x+3=2x-5+x | | (-3)+(7)=x | | 11+6x=35 | | (-7)+(-3)=x | | x^2+2x+7=6x+3 | | (x-8)(5x+6)=(x-10)(x-2) | | 12=n/4+8 | | 9x+4=-6x+-17 | | (3-c^2d)(4-4c^2d)=0 | | y+5=0.5x | | -38=5v-3 | | x^2+4x-1=7x+9 | | 4x+13=93 |